2013
DOI: 10.1038/cddis.2013.168
|View full text |Cite
|
Sign up to set email alerts
|

Preferential killing of human lung cancer cell lines with mitochondrial dysfunction by nonthermal dielectric barrier discharge plasma

Abstract: The distinctive cellular and mitochondrial dysfunctions of two human lung cancer cell lines (H460 and HCC1588) from two human lung normal cell lines (MRC5 and L132) have been studied by dielectric barrier discharge (DBD) plasma treatment. This cytotoxicity is exposure time-dependent, which is strongly mediated by the large amount of H2O2 and NOx in culture media generated by DBD nonthermal plasma. It is found that the cell number of lung cancer cells has been reduced more than that of the lung normal cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(167 citation statements)
references
References 36 publications
5
158
0
4
Order By: Relevance
“…11b by the mutual interaction of hydroxyl OH species with lung cancer cells, where the hydroxyl OH radicals are produced inside the solution by the plasma treatment on the solution surface. With adjustment of experimental conditions, it is found that the threshold OH density for apoptosis of H460 cells inside the DMEM is about 0.3 9 10 16 cm -3 under 1 min plasma exposure, which may be followed by mitochondrial damages as reported previously [25].…”
Section: Density Of Hydroxyl Oh Radical Species and Its Influence Onsupporting
confidence: 67%
“…11b by the mutual interaction of hydroxyl OH species with lung cancer cells, where the hydroxyl OH radicals are produced inside the solution by the plasma treatment on the solution surface. With adjustment of experimental conditions, it is found that the threshold OH density for apoptosis of H460 cells inside the DMEM is about 0.3 9 10 16 cm -3 under 1 min plasma exposure, which may be followed by mitochondrial damages as reported previously [25].…”
Section: Density Of Hydroxyl Oh Radical Species and Its Influence Onsupporting
confidence: 67%
“…The activation of caspase-3 has been observed during apoptotic cell death in many types of cancer cells in previous studies as well [38]. In addition, many researchers have reported that the tumor cell selectivity of non-thermal plasma was compared between normal cells and cancer cells such as skin cancer cells [39], lung cancer cells [40], glioma cells [41], and ovarian cancer cells [42]. From these previous reports, we suggest that non-thermal plasma specifically induces the oncogenic colon cell death or has mild effects on non-oncogenic cells.…”
Section: Discussionmentioning
confidence: 90%
“…optical emission spectroscopy) za detekciju kemijski aktivnih vrsta, deaktivacija biofilmova na Ti diskovima promatrana je fluorescencijskom mikroskopijom kao i pretražnim elektronskim mikroskopiranjem (SEM, engl. scanning electron microscopy), termalne sonde koriste se za mjerenje temperature plazme i određivanje prenesene toplinske energije, a spektrometrijom izotopnih omjera promatraju se izotopne promjene u plazmom tretiranim tekućinama [11][12][13][14][15][16][17] . Nastojanja da se konstruira što bolji instrument za CAP generiranje rezultirala su mnogobrojnom aparaturom različite konfiguracije i posljedično, mnogobrojnim geometrijama plazme: plazmena igla (engl.…”
Section: Plazma U Fiziciunclassified
“…Stanice tumora osjetljive su na egzogene ROS zbog čega se nametnula ideja tretmana CAP-om kao alternative zračenju i kemoterapiji u tretiranju tumora 12,41 . Utjecaj tretmana CAP-om na stanice tumora intenzivno se istražuje, što je rezultiralo velikim brojem studija u kojima su korišteni različiti izvori CAP-a i mnogobrojne stanič-ne linije izvedene iz različitih tumorskih tkiva 42,43 .…”
Section: Moguća Primjena U Terapiji Tumoraunclassified